Exploring midwives’ practice patterns and capacity for obstetric ultrasound imaging: Towards a multicentre longitudinal materno-foetal research readiness in a low-resource setting - Albert Dayor Piersson; Philomena Ajanaba Asakeboba; Sarah Teiko Quartei; Rachel Mendy; Joseph Arkorful; Ama Boahene Akomah; Gilbertson Allorsey (PLoS ONE, 2026)
Introduction Midwives are often the first point of contact for pregnant women; yet their roles, training, and referral practices regarding obstetric ultrasound vary widely. This study aimed to explore midwives’ perspectives and experiences with obstetric ultrasound across key clinical and operational domains to assess the feasibility of conducting future multicentre maternal-foetal health research and surveillance. Methods A descriptive cross-sectional study was conducted among 475 practicing midwives across diverse healthcare settings in Ghana. A self-administered structured questionnaire was used to collect data on midwives’ perspectives and experiences regarding obstetric ultrasound across multiple dimensions. Data analysis was performed using Microsoft Excel. Results Most midwives were female, aged 26–35 years, held diploma qualifications, and practiced within district hospitals. Key ultrasound measures prioritised by midwives in the 1 st trimester include gestational age, foetal viability, estimated date of delivery (EDD), number of foetuses, and the presence of an intrauterine gestational sac. Comparatively, midwives emphasize foetal anomaly detection, amniotic fluid (liquor) volume, placental location, foetal viability, and gestational age during second trimester ultrasound screening, while in the 3 rd trimester screening, they prioritise foetal presentation, amniotic fluid volume, estimated foetal weight, placental location, and foetal viability. Findings suggest infrequent ultrasound reports indicating foetal anomalies. We observed a moderate perceived ability among midwives to understand foetal anomalies on obstetric ultrasound reports. Only 57.5% indicated they refer patients between one and three times for obstetric ultrasound before delivery. From the findings, it was observed that there is a predominance of sonographers undertaking obstetric ultrasound scans. Midwives may have moderate competence in interpreting obstetric ultrasound reports. An overwhelmingly positive response indicated that obstetric ultrasound improved their work performance, and a high proportion expressed interest in learning how to undertake obstetric ultrasound. Conclusion Our findings highlight the need to standardize midwifery practices and strengthen obstetric ultrasound literacy through targeted capacity-building initiatives, not only to improve clinical decision-making but also to establish a robust foundation for scalable maternal-foetal research in low-resource settings. Additionally, our study demonstrates the potential feasibility of engaging midwives as key stakeholders in multicentre maternal-foetal research initiatives.